Muscle Pathology Associated With Cardiac Function in Duchenne Muscular Dystrophy - Jin A Yoon; Heirim Lee; In Sook Lee; You Seon Song; Byeong-Ju Lee; Soo-Yeon Kim; Yong Beom Shin (Annals of Rehabilitation Medicine)
Objective To compare the progression of muscle fibrosis of various site and its relation between cardiac deterioration in Duchenne muscular dystrophy (DMD). In this study aimed to examine the associations between echocardiogram-based cardiac function indices and fibrosis of the abdominal and lower extremity muscles in patients with DMD to facilitate early detection of cardiac dysfunction and identify its predictors. Methods Twenty-one patients with DMD patients were enrolled in the study. The association between cardiac dysfunction and fibrosis of the abdominal and lower extremity muscles was determined by analyzing the echocardiography and elastography. Non-parametric Spearman rank correlation coefficients were used to examine the pairwise relationships between cardiac function and muscle elasticity. Results All patients were male and non-ambulant. Their mean age was 18.45±4.28 years. The strain ratios of the abdominal muscle and quadriceps muscles were significantly higher than those of the medial gastrocnemius. The strain ratio of the rectus abdominis muscle has a significant negative correlation with left ventricular ejection fraction. Cardiac function and valvular insufficiency were not significantly correlated with muscle strain ratio. According to the result of our study, the only skeletal muscle which showed significant correlation with cardiac dysfunction was degree abdominal muscle fibrosis. Conclusion The degree of fibrosis of respiratory muscles was also significantly associated with cardiac dysfunction; therefore, it can be used as a predictor of cardiac dysfunction in patients with DMD in clinical practice.